2023
DOI: 10.7554/elife.81808
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide participation in FIT-based colorectal cancer screening in Denmark during the COVID-19 pandemic: An observational study

Abstract: Background: Worldwide, most colorectal cancer screening programmes were paused at the start of the COVID-19 pandemic, whilst the Danish faecal immunochemical test (FIT)-based programme continued without pausing. We examined colorectal cancer screening participation and compliance with subsequent colonoscopy in Denmark throughout the pandemic. Methods: We used data from the Danish Colorectal Cancer Screening Database among individuals aged 50-74 years old invited to participate in colorectal cancer screening fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
2
2
0
Order By: Relevance
“…This indicates that the restrictions imposed in Denmark may have affected some groups of women disproportionally. A study from Spain Bosch et al, 2022 found that the participation in mammography screening decreased with age and with lower socio-economic level post-COVID-19; this has also been reported for the two other screening programmes in Denmark ( Olesen et al, 2023a ; Olesen et al, 2023b ; this study). The evidence is scarce on participation according to ethnicity throughout the pandemic; however, the lower participation during the pandemic has also been demonstrated for bowel and cervical cancer screening in Denmark ( Olesen et al, 2023a ; Olesen et al, 2023b ; this study).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This indicates that the restrictions imposed in Denmark may have affected some groups of women disproportionally. A study from Spain Bosch et al, 2022 found that the participation in mammography screening decreased with age and with lower socio-economic level post-COVID-19; this has also been reported for the two other screening programmes in Denmark ( Olesen et al, 2023a ; Olesen et al, 2023b ; this study). The evidence is scarce on participation according to ethnicity throughout the pandemic; however, the lower participation during the pandemic has also been demonstrated for bowel and cervical cancer screening in Denmark ( Olesen et al, 2023a ; Olesen et al, 2023b ; this study).…”
Section: Discussionsupporting
confidence: 81%
“…A study from Spain Bosch et al, 2022 found that the participation in mammography screening decreased with age and with lower socio-economic level post-COVID-19; this has also been reported for the two other screening programmes in Denmark ( Olesen et al, 2023a ; Olesen et al, 2023b ; this study). The evidence is scarce on participation according to ethnicity throughout the pandemic; however, the lower participation during the pandemic has also been demonstrated for bowel and cervical cancer screening in Denmark ( Olesen et al, 2023a ; Olesen et al, 2023b ; this study). Immigrants may find it more difficult to navigate the healthcare system in Denmark, and possibly this has been exacerbated by the pandemic where the majority of the communication at press conferences and news media were conveyed in Danish, a language that may not be fully comprehensive to all immigrants.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…1 In 2021, the COVID-19 project was launched in Denmark to investigate the secondary consequences of the pandemic on various illnesses. [2][3][4][5][6] The study was conducted by the Danish Clinical Quality Program -National Clinical Registries (RKKP) in partnership with medical professionals. The primary goal of the project was to gain insight into how the pandemic affected the following areas: the levels of diagnostic and therapeutic activity for illnesses besides COVID-19, the quality of care for diseases other than COVID-19, social inequality in healthcare, and the lessons learned for managing similar pandemics and catastrophes in the future.…”
Section: Referencesmentioning
confidence: 99%